Can galactic dark matter substructure contribute to the cosmic gamma-ray anisotropy? - Lange, Johannes; Chu, Ming Chung (Monthly notices of the Royal Astronomical Society, 2015)
The annihilation of dark matter (DM) particles in the Milky Way can contribute to the diffuse gamma-ray background (DGRB). Due to the presence of substructures, this emission will appear anisotropic in a predictable way. We generate full-sky maps of the gamma-ray emission in galactic substructures from results of the high-resolution Via Lactea II N-body simulation of the Milky Way DM halo. We calculate the anisotropy pattern, taking into account different radial profiles of the DM distribution in substructures, cosmic variance, and the detection threshold, and compare it to the anisotropy in the DGRB observed by the Fermi Large Area Telescope (LAT).
Published: 19 December 2014
Gesehen am 09.06.2020